FINANCIAL RATIOS AND FIRM VALUE OF FOOD & BEVERAGE COMPANIES BEFORE AND AFTER COVID-19 - Muhammad Ghusti Rakha Pratama; Tanti Handriana (Asosiasi Dosen Muda Indonesia, 2024)
This study examines the firm values (Tobin's Q) which are affected by a few financial ratio parameters, including profitability using return-on-equity (ROE), asset management using total asset turnover (TATO), and leverage using debt-to-equity ratio (DER) before and after the Covid-19 period. The population used in this study were 42 non-cyclic consumer manufacturing sub-sector companies with F&B products listed on the Indonesia Stock Exchange during the 2019-2022 period. The data collection used in this study is by secondary collection method from annual financial reports and the official website of each company. The study's findings showed that DER and TATO respectively did not significantly affect firm value, while ROE had a favorable and noteworthy effect on company value both sometime recently and after the COVID-19 pandemic. This study is more recent after COVID-19 so it can describe the most real conditions.